Professional JavaScript : fast-track your web development career using the powerful features of advanced JavaScript - Di Francesco, Hugo (Packt Publishing, 2019)
Develop your JavaScript programming skills by learning strategies and techniques commonly used in modern full-stack application development Key Features Write and deploy full-stack applications efficiently with JavaScript Delve into JavaScript's multiple programming paradigms Get up to speed with core concepts such as modularity and functional programming to write efficient code Book Description In depth knowledge of JavaScript makes it easier to learn a variety of other frameworks, including React, Angular, and related tools and libraries. This book is designed to help you cover the core JavaScript concepts you need to build modern applications. You'll start by learning how to represent an HTML document in the Document Object Model (DOM). Then, you'll combine your knowledge of the DOM and Node.js to create a web scraper for practical situations. As you read through further lessons, you'll create a Node.js-based RESTful API using the Express library for Node.js. You'll also understand how modular designs can be used for better reusability and collaboration with multiple developers on a single project. Later lessons will guide you through building unit tests, which ensure that the core functionality of your program is not affected over time. The book will also demonstrate how constructors, async/await, and events can load your applications quickly and efficiently. Finally, you'll gain useful insights into functional programming concepts such as immutability, pure functions, and higher-order functions. By the end of this book, you'll have the skills you need to tackle any real-world JavaScript development problem using a modern JavaScript approach, both for the client and server sides. What you will learn Apply the core concepts of functional programming Build a Node.js project that uses the Express.js library to host an API Create unit tests for a Node.js project to validate it Use the Cheerio library with Node.js to create a basic web scraper Develop a React interface to build processing flows Use callbacks as a basic way to bring control back Who this book is for If you want to advance from being a frontend developer to a full-stack developer and learn how Node.js can be used for hosting full-stack applications, this is an ideal book for you. After reading this book, you'll be able to write better JavaScript code and learn about the latest trends in the language. To easily grasp the concepts explained here, you should know the basic syntax of ...